2007
DOI: 10.1130/ges00076.1
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogic and textural analyses of drill cuttings from the San Andreas Fault Observatory at Depth (SAFOD) boreholes: Initial interpretations of fault zone composition and constraints on geologic models

Abstract: We examine drill cuttings from the San Andreas Fault Observatory at Depth (SAFOD) boreholes to determine the lithology and deformational textures inthe fault zones and host rocks. Cutting samples represent the lithologies from 1.7-km map distance and 3.2-km vertical depth adjacent to the San Andreas Fault. We analyzed two hundred and sixty-six grain-mount thin-sections at an average of 30-m-cuttings sample spacing from the vertical 2.2-km-deep Pilot Hole and the 3.99-km-long Main Hole. We identify Quaternary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 64 publications
(110 reference statements)
3
88
1
Order By: Relevance
“…1a; Zoback et al, 2011). Within the SAFOD drill holes four major geological units have been identified (Bradbury et al, 2007) with Quaternary and Tertiary sediments, Salinian granite and arkosic sediments beneath the Buzzard Canyon fault. Approximately 1200 m NE of the drill site the arkosic sediments of the Salinian block (Pacific plate) are replaced by shales and siltstones of the Great Valley/Franciscan sequence (North American plate).…”
Section: The Safod Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…1a; Zoback et al, 2011). Within the SAFOD drill holes four major geological units have been identified (Bradbury et al, 2007) with Quaternary and Tertiary sediments, Salinian granite and arkosic sediments beneath the Buzzard Canyon fault. Approximately 1200 m NE of the drill site the arkosic sediments of the Salinian block (Pacific plate) are replaced by shales and siltstones of the Great Valley/Franciscan sequence (North American plate).…”
Section: The Safod Projectmentioning
confidence: 99%
“…The main drill hole crosscuts multiple faults including two actively creeping strands, the Southwest Deforming Zone (SDZ) and the Central Deforming Zone (CDZ) (Fig. 1b;Zoback et al, 2010), which were revealed by pronounced and ongoing casing deformation (Bradbury et al, 2007;Zoback et al, 2010). Detailed descriptions of SAFOD Phase 3 core material from Holes E and G (Fig.…”
Section: The Safod Projectmentioning
confidence: 99%
“…This drilling extended into interbedded mudstone, siltstone and shale lithologies at the bottom of the drill hole (Figure 1c) [Draper et al, 2005;Hickman et al, 2005]. Bradbury et al [2007] investigated the bulk mineralogy of the SAFOD drill cuttings, showing an arkosic rock sequence from 1920 to 2550 m, separated by a clay rich zone at 2530-2680 m and a fine-grained sequence at 2680-3150 m MD. A lithologic change occurs at $3150 m MD, where arenites are replaced by fine-grained siltstone and shaly fragments.…”
Section: San Andreas Fault and The Safod Drill Holementioning
confidence: 99%
“…The appearance of chlorite and chlorite-smectite (C-S) minerals at $3150 m MD reflects the lithologic change from finer grained arkosic sandstones to a fine-grained quartz-feldspar-rich siltstone that alternates with sandy and shaly sections [Draper et al, 2005;Bradbury et al, 2007]. The picked fault-related grain material comprises fine-grained mudrock lithologies containing abundant illite and I-S along with quartz and plagioclase components in the shallow fault trace.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
See 1 more Smart Citation